Modeling of airport rigid pavement structure made of RCC and recycled cement concrete for complex configuration of landing gears - Cojocaru, Radu (2013)
This paper presents the results of the research undertaken by the authors in the frame of the postdoctoral program 4D-POSTDOC. After a short introduction on the actual status of structural design of airport pavements including geometrical and loading characteristics of complex loading gears, the modeling and the structural design of airport rigid pavements, constructed with conventional and various recycled materials, using the finite element method, is described. The main objective of this research program was to elaborate a design method which, beside the complex landing gear including six footprint tires, all specific parameters related with the recycled materials and with conventional and reinforce rolled compacted concrete (RCC) technologies are included. Finally, practical design diagrams for structural design of the concrete slabs, including their specific correlation function, used for the construction of the Airbus-A380 runway are presented.